Resoconto sul Convegno Nazionale SIRD 2023: «La SIRD tra passato, presente e futuro. Il ruolo della ricerca educativa ai tempi del COVID, della terza guerra mondiale, della globalizzazione e della crisi ecologica» - Conny De Vincenzo (LED Edizioni Universitarie, 2023)
The National Conference «SIRD between past, present and future. The role of educational research in the times of COVID, world war III, globalization and the ecological crisis» was organized by the Italian Society of Educational Research (SIRD). The conference was organized on the occasion of SIRD's 30th anniversary and aimed to foster active discussions on the key challenges that educational research has encountered in recent years. The event started with a plenary session that retraced the significant milestones that characterized the founding of SIRD, featuring speeches from past presidents of the society. Following, the conference delved into thematic working groups, which focused on relevant research topics including Teaching Learning Centers, PNRR and guidance, career access and progression, university teaching, research and teacher training, internationalization, 11/D2 coordination, doctoral training, quality of publications, and internationalization of journals. This paper provides a summary of the conference's primary discussions, highlighting their relevance within the context of contemporary educational research.